Oxidation desulfurization of model oil using carbon composite derived from peach stone waste - Hashim Abood, Esraa; Al-Jendeel, Haider A.; Al-Salihi, Sara (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
In this study, oxidative desulfurization of dibenzothiophene (DBT) with H2O2 as an oxidant was studied, whereas the catalyst used was zirconium oxide supported on Activated carbon (AC). Zirconium oxide (ZrO2) was impregnated over prepared activated carbon (AC) and characterized by various techniques such as XRD, FTIR, BET, SEM, and EDX. This composite was used as a heterogeneous catalyst for oxidation desulfurization of simulated oil. The results of this study showed that ZrO2/AC composite exhibited significant catalytic activity and stability, effectively lowering sulfur content under mild conditions. Factors such as reaction temperature (30, 40, 50, 60°C), time (5, 10, 15,20,30,60, 80 100 min), catalyst dose (0.3, 0.5, 0.7, 0.9 g) and initial concentration of dibenzothiophene (DBT) (20,40, 60, 80, 100, 200, 300 ppm) was used to achieved maximum efficiency. 10 ml of H2O2 /100 ml of simulated oil was used as an oxidizing agent. It was found that an increase in all the above variables led to an increase in desulfurization efficiency, except for an increase in initial DBT concentration, which led to a decrease in removal efficiency. The maximum removal efficiency of sulfur content was 92.22%, which was achieved at 60 °C and 0.9g of composite /100 ml of simulated oil at equilibrium time 100 min and 100ppm initial concentration of DBT. Finally, the reaction kinetics matched the pseudo-second order rate model, with an activation energy of 36.665 KJ/mol.